Interaksi Simbolik dalam Kehidupan Keluarga Petani: Makna Simbolik dan Pengelolaan Sumber Daya Alam di Desa Setupatok - Viqia Sastrawardana; Rheina Sabrina Az-Zahra; Gupita Sevia Salsabila; Vanzi Galileo; Parha Nurahman (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to explore the symbolic meaning of life in local wisdom with a focus on farming families in Setupatok Mundu Cirebon. Researchers explored this study using qualitative research, through a non-participatory observation approach. The results showed that life in a symbolic context is defined as the way they interact with the outdoors as a form of adjustment to fulfill their needs. Elements of local wisdom are also emphasized through the habitual patterns of Setupatok farmers in the use of their agricultural system which relies on traditional tools. By enjoying the crops owned by farming families, this research symbolically interprets life in the outdoors. This research provides a comprehensive understanding of symbolic interaction, defining symbolic interaction as our attempt to understand human behavior based on their own point of view.